MEDIATION PROCEDURE WHILE CONSIDERING HOUSING DISPUTES (Bulletin of criminological association of Ukraine, 2024)
The article identifies the specifics of the mediation procedure in resolving housing disputes. It is noted that the institution of mediation serves as one of the means of protecting rights within the framework of non-jurisdictional forms of legal protection, particularly in civil, family, and housing matters. It is indicated that housing disputes encompass conflicts regarding: housing privatization; forced eviction from housing; occupancy of housing; acquisition of housing rights; preservation of the housing stock; termination of lease agreements; cessation of residential servitudes; provision of housing and communal services. It is determined that mediation can be applied: 1) at the onset of a dispute, as a preventive measure (the mediator will undertake functions to shape the parties' will aimed at preventing conflict and ensuring their lawful behavior); 2) as a procedure for resolving an existing dispute (the mediator enters into the dynamics of the contentious legal relationship, with their function directed towards protecting rights and restoring the regime of legality). Alternative dispute resolution is conducted within the framework of the mediation procedure. Dispute resolution can be achieved through the conclusion of a mediation agreement. It is emphasized that mediation is terminated as a result of: the expiration of the mediation period and/or the expiration of the mediation agreement; premature termination of the mediation procedure (in case of refusal by at least one of the mediation parties or the mediator(s) to participate in mediation); 3) the practical impossibility of further mediation procedure (in case of the death of a natural person who is a party to mediation, or the liquidation of a legal entity that is a party to mediation; in case of recognition of a mediation party or mediator(s) as legally incapacitated or as a person whose civil capacity is limited).
Keywords: mediation; form of protection; means of protection; housing; dispute resolution; mediation agreement; mediation procedure; mediator